Perbedaan Motivasi Belajar dan Prestasi Antara Siswa SMP Kelas Imersi dan Reguler - Fadlilah, Shobichah Nurul (JURNAL KONSELING GUSJIGANG, 2023)
This study discusses how the implementation of the teaching and learning process with the facilities provided in the immersion and regular classes, the quality of students in the regular and immersion classes, so as to have an influence on student motivation and achievement, as well as what efforts can be provided by guidance and counseling services. on the effect of learning motivation and achievement between immersion and regular class students at the junior high school level. This study uses a qualitative descriptive research method. The research subjects in this study were students at  SMP Negeri 1 Rembang with a sample size of 20 students. From the results of the analysis obtained, it can be concluded that the difference between the immersion class and the regular class greatly affects the level of learning motivation and achievement in students, such as there is a higher increase in motivation and interest in learning in the immersion class compared to the regular class after the provision of learning guidance and counseling services. , most of the responses from immersion class students stated that learning guidance and counseling services were able to improve students' academic achievement than regular classes, and in terms of providing class facilities it was different. However, it is possible that the quality of the regular class is also better than the immersion class, so that the regular class students will also have learning motivation and achievements that are not far inferior to the immersion class.